2013
DOI: 10.1111/pbr.12077
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐assisted simultaneous but stepwise backcross breeding for pyramiding blast resistance genes Piz5 and Pi54 into an elite Basmati rice restorer line ‘PRR78’

Abstract: Marker‐assisted simultaneous but stepwise backcross breeding (MASS‐BB) was utilized in the present study for pyramiding blast resistance genes, Piz5 and Pi54, from non‐Basmati donors, C101A51 and Tetep, respectively, into PRR78, an elite Basmati restorer line of rice hybrid, Pusa RH10. Marker‐assisted foreground selection coupled with stringent phenotypic selection and background analysis was carried out for hastening the recovery of recurrent parent phenome (RPP) and genome (RPG) in two separate backcross ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 27 publications
(70 reference statements)
1
63
0
Order By: Relevance
“…From the background analysis, the RPG recovery was found up to 91.6% in BC 2 F 1 generation for pyramiding blast resistance genes Piz5 and Pi54 into an elite Basmati rice restorer line 'PRR78' using marker-assisted stepwise backcross breeding [18]. The mean RPG recovery in BC 2 generation using computer simulated 97% in case of Swarna and Samba Mashuri; observed 95% in case of Swarna and Samba Mashuri [43].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…From the background analysis, the RPG recovery was found up to 91.6% in BC 2 F 1 generation for pyramiding blast resistance genes Piz5 and Pi54 into an elite Basmati rice restorer line 'PRR78' using marker-assisted stepwise backcross breeding [18]. The mean RPG recovery in BC 2 generation using computer simulated 97% in case of Swarna and Samba Mashuri; observed 95% in case of Swarna and Samba Mashuri [43].…”
Section: Discussionmentioning
confidence: 98%
“…It is evident from the results that phenotypic selection for agro-morphological traits of MR219 coupled with marker-assisted background analysis led to hastening the recurrent parent genome and phenome recovery. The use of MAS for background selection can be very effective when the number of polymorphic markers included in the study is large, but with only 20% SSR polymorphism between the parental lines, MAS for background selection is still a distant dream for resource-limited laboratories [18]. In that case, stringent phenotypic selection for the RPP recovery is a very feasible option for the maximization of RPG recovery [53,54].…”
Section: Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher recovery of RPG was achieved mainly through stringent phenotypic selection followed by background selection using molecular markers. Background analysis exercised through phenotypic evaluation is reported to be useful in efficient recovery of the RPG [48]. It has been suggested that stringent phenotypic selection for the recovery of recurrent parent phenotype is a good substitute for background selection through molecular markers in terms of judicious use of resources [42,[49][50][51].…”
Section: Marker Assisted Background Selection With Stringent Phenotypmentioning
confidence: 99%
“…However, the introgression of resistant genes without maintaining or improving yield levels and the grain quality would offer no reward; as such, varieties would not be adopted by farmers. Different MAS approaches are now, in practice, using background and foreground selection [20,21], as well as combined approaches utilizing foreground selection with stringent phenotypic selection [22], and foreground selection coupled with stringent phenotypic selection and background analysis [21]. Such practices have aided in accurate and efficient gene transfer, including gene pyramiding, into desired varietal backgrounds.…”
Section: Discussionmentioning
confidence: 99%